AB0907 Epidemiological Features of Childhood IGA Vasculitis (Henoch–Schönlein) in a French County: A Population-Based Survey. (10th June 2014) - Piram, M.; Biscardi, S.; Desuremain, N.; Djaffar, H.; Georget, E.; Regnard, D.; Kone-paut, I.; Mahr, A.
Abstract : Background: Immunoglobulin A vasculitis (IgAV, Henoch–Schönlein) is the most common childhood vasculitis in western countries. Population-based studies mainly carried out in Europe over the last 4 decades reported annual incidence rates of 3 to 27 per 100, 000 children (1). The etiology of IgAV remains unclear. Incidence peaks in the colder months suggested an infectious underpinning, although genetic susceptibility and other environmental triggers might also play a role. More epidemiological studies are required to determine potential changes over time in the epidemiological characteristics of IgAV. Objectives: To describe the epidemiological characteristics of childhood IgAV in a large French population. Methods: Cases were prospectively collected in Val de Marne county, a southeastern suburb of Paris, with 258, 255 residents <15 years old. Children with incident IgAV living in this area during 2012 and 2013 were identified by 3 sources of case notification (emergency departments, pediatrics departments, private practice pediatricians). Diagnoses were verified against the EULAR/PRINTO/PRES criteria. We calculated 95% confidence intervals (95% CIs) for incidence rates under the assumption of a Poisson distribution. Seasonal variations in IgAV incidence were investigated by comparing observed to expected frequencies by chi-square testing. Results: The survey identified 80 incident cases meeting the study criteria, including 42 (55%) boys and 35 (45%) girls (3 missing values) with a mean age of 6.7 years (standard deviation: 2, 6 years; range 2.9–14.8 years). The overall annual incidence (per 100, 000 children) was 15.5 (95% CI 12.7–24.2), with 15.9 (9.8–24.3) for boys and 13.9 (8.5–22.5) for girls. The annual distribution of diagnoses (spring: 27%, summer: 10%, fall: 28%, winter: 36%) significantly deviated from a random distribution ( P =0.01) and indicated a higher incidence in fall or winter as compared with spring or summer ( P =0.02). Clinical manifestations at presentation included purpura (100%), urticaria (15%), arthralgias/arthritis (94%), acral edema (66%), abdominal involvement (54%), scrotal edema (10%) and renal involvement (16%). Abdominal manifestations included pain (48%), vomiting (26%), anorexia (25%), diarrhea (12%), hemorrhage (8%) and intussusception (1%). Renal involvement was mostly mild and diagnosed from findings of proteinuria and hematuria (15%); only 2 children (3%) underwent renal biopsy. Conclusions: The annual incidence rate of 15.5 per 100, 000 children, gender distribution and seasonal variation we observed are in line with data reported from other geographic areas and time periods. In contrast, the small proportion and mild presentation of IgAV-associated renal disease supports the rather benign profile of IgAV at the population level. References: Piram M, Mahr A. Epidemiology of immunoglobulin A vasculitis (Henoch-Schönlein): current state of knowledge. Curr Opin Rheumatol 2013;25:171-8 Acknowledgements: The authors are indepted to all of the hospital and private practice pediatricians contacted for this study for help in retrieving IgAV cases. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4706